POLITENESS IN INTERLANGUAGE REFUSALS BY ENGLISH TEACHERS IN INDONESIA - Maya Hartuti (Kajian Linguistik dan Sastra, 2015)
This paper is a part of a larger scale interlanguage pragmatic study exploring politeness involved in refusals conducted by the English teachers in East Java, Indonesia. The data were elicited by discourse completion tasks (DCT), from 38 English teachers, (n=14 males and n=24 females). The empirical data of politeness strategies were analyzed by Brown and Levinson’s (1987) theory. The findings showed that the EFL teachers applied two semantic formulae indirect and direct strategies in conjunction to adjuncts across three initiating acts of refusals (invitations, offers and suggestions). When declining invitations and suggestions, they mostly applied positive politeness, but when refusing offers they predominantly used bald on record.  Keywords: Politeness, interlanguage pragmatics, refusal strategy